2011
DOI: 10.1111/j.1742-4658.2011.08003.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the N‐terminal region of TjZNT2, a Zrt/Irt‐like protein family metal transporter, as a novel functional region involved in metal ion selectivity

Abstract: The Zrt/Irt‐like protein (ZIP) family of transporter proteins is involved in the uptake of essential metal elements in plants. Two homologous ZIP genes from Thlaspi japonicum, TjZNT1 and TjZNT2, encode products that share high amino acid sequence similarity except at the N‐terminus and the cytoplasmic loop between transmembrane domains III and IV, and that have been shown to be Zn2+ and Mn2+ transporters, respectively. To identify the region that determines the ion selectivity of these transporters, we constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The Ni uptake assay was performed as described previously (Nishida et al 2008, Nishida et al 2011, except that 50 mM CdCl 2 was substituted for 500 mM NiCl 2 .…”
Section: Metal Uptake Assays In Yeastmentioning
confidence: 99%
“…The Ni uptake assay was performed as described previously (Nishida et al 2008, Nishida et al 2011, except that 50 mM CdCl 2 was substituted for 500 mM NiCl 2 .…”
Section: Metal Uptake Assays In Yeastmentioning
confidence: 99%
“…for Zn 2+ and Mn 2+ ) in the ZIP family proteins. 10 As far as functional regions involved in metal ion selectivity are concerned, the loop between the transmembrane domains II and III should be considered. It has been shown that the replacement of a Glu residue at position 103 in wild-type IRT1 protein (ZIP family) with Ala changes the substrate specificity of the transporter by selectively eliminating its ability to transport Zn 2+ .…”
Section: Introductionmentioning
confidence: 99%